Legal Status of Joint Property that Remains Subject to Security Interests After Divorce - Tyur Reggina Dewanti; Taupiqqurrahman Taupiqqurrahman (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Marriage not only creates legal bonds between husband and wife, but also has legal consequences for property, in this case joint property. In practice, joint property is often used as collateral to obtain credit from financial institutions. When a divorce occurs while the property is still pledged to a third party, legal issues arise regarding the status of joint property and responsibility for debt repayment after divorce. This study aims to determine the legal status of joint property that is still used as collateral after divorce and the responsibility for debt repayment on the collateral. The researcher applied and utilized a normative juridical method with an approach that focused on legislation and was supported by interviews with the Junior Clerk of the East Jakarta Religious Court as supporting data in the study. The results of the study show that the legal status of joint property that is still collateralized remains as joint property after divorce, but the distribution cannot be carried out before the obligations to third parties are settled because it is still bound by collateral rights. This is because collateral has the characteristics of droit de suite and the provisions of SEMA 2018. The responsibility for paying off debts is a joint obligation of the former husband and wife. If there is a refusal or even inability to pay, the settlement is carried out through an auction by the creditor, while the remaining proceeds from the auction after the debt has been paid off become part of the joint property, which will then be distributed in accordance with applicable legal provisions.